Do the Ticks of Birds at an Important Migratory Hotspot Reflect the Seasonal Dynamics of Ixodes ricinus at the Migration Initiation Site? A Case Study in the Danube Delta - Sándor, Attila D. (Public Library of Science, 2014)
Migratory birds play important roles as distributors of ticks within and between continents. In the Old World, the most important migratory route of birds links Asia, Europe and Africa. During their migration, birds use various stopover sites, where they feed and rest and where ticks may attach or detach, creating new natural foci for vector-borne diseases. Danube Delta is one of the most important migration hotspots and so far no studies were focused on ticks of migratory birds herein. The aim of the present study was to assess the species diversity and seasonal dynamics of ticks parasitizing migratory birds in Danube Delta Biosphere Reserve. Migratory birds were trapped on Grindul Lupilor (44°41′N; 28°56′E) using mist nets during 4 migratory seasons (2 spring and 2 autumn) in 2011 and 2012. From each bird, all the ticks were collected and identified based on morphological features. Epidemiological parameters (prevalence, mean abundance, mean intensity) were calculated and all data were analysed statistically based on the season (spring and autumn), regional status of birds (migrants and breeding) and foraging behaviour (ground feeders, reed-bed feeders, foliage feeders). A total of 1434 birds (46 species) were captured. Ticks were found on 94 birds (10 species). Significantly more migratory birds hosted ticks, compared to resident birds. The 400 collected ticks belonged to four species: Ixodes ricinus (92.25%), I. arboricola (6.25%), I. redikorzevi (1.00%) and Haemaphysalis punctata (0.50%). A higher prevalence was found for I. ricinus in spring, with higher prevalence of nymphs in this season, while larvae occurred with the same prevalence in both seasons. Larval intensity was higher during spring and nymphs were more abundant during autumn. The seasonal differences in our study may be related not to the local seasonal dynamics of ticks, but on the seasonal dynamics at the site of migration initiation.